SYSTEMATICAL REVIEW OF CORROSION INHIBITOR APPLICATION IN CARBON STEEL PIPE TRANSPORTING SUPERCRITICAL CARBON DIOXIDE IN CARBON CAPTURE STORAGE (CCS) FACILITY - AGUNG NUGRAHA, ROSADI
The increase in emissions of carbon dioxide gas (CO2) is in highly alarming rate, and with it’s dangerous effect it is needed to lower CO2 content in atmosfer. Even though the world is turning to renewable energy, dependence on fossil fuels for transportation and electricity generation is still difficult to change. As an alternative, the idea of using a Carbon Capture Storage (CCS) facility to capture, transport, and store CO2 emissions is promising. In transporting CO2 from sources (such as power plants, industrial combustion, etc.) to the storage, transportation usually uses carbon steel pipes with the condition that the CO2 flow is in a supercritical phase. Apart from its economical price, carbon steel pipes have the threat of suffered from internal corrosion due to supercritical CO2 (SC-CO2). The use of corrosion inhibitors for carbon steel in the SC-CO2 environment still needs to be studied because the corrosion environment is very different from the common sweet corrosion (in a non-supercritical phase). Therefore, the inhibition mechanism of SC-CO2 corrosion in carbon steel pipes and the criteria for an efficient inhibitor is discussed in this study. The results show the conclusion that so far three types of compounds have been proven to be used as corrosion inhibitors in SC-CO2 carrier carbon steel pipes, namely ammonia direct derivatives (urea and amines), azole derivatives, and pyrimidine derivatives. These three compounds are known to be mixed-type inhibitors which tend to be anodic and protect them by forming a thin layer through chemisorption and / without physisorption. The use of azole derivatives, namely imidazoline, needs to be added with a modifier (such as Thiosulfate or H2S, and KI) so that the imidazoline can be adsorbed effectively on the positively charged carbon steel surface when SC-CO2 is applied. Meanwhile, 2-Mercapto-(benzo)thiazole (MBTH) as a thiazole derivative compound can adapt by forming MBT- ions. The use of direct ammonia derivatives (urea and amines) can provide a neutralizing effect on pH due to the tendency of the inhibitor to bind hydrogen ions. The use of a pyrimidine derivative, that is 4,6-diamino-2-(benzylthio)pyrimidine (DABTP), can inhibit carbon steel by forming a DABTP-complex due to its polar nature. In general, the criteria for an inhibitor that is suitable for corrosion inhibition of carbon steel pipes carrying SC-CO2 must be stable in dynamic conditions (there is flow), be able to adsorb well on the surface of positively charged carbon steel, resistant to impurities carried by the flow of SC-CO2, as well as providing optimum inhibition efficiency in both the supercritical phase and the aqueous phase.